In-situ investigation and modeling of electrochemical reactions with simultaneous oxygen and hydrogen microbubble evolutions in water electrolysis. (25th October 2019) - Li, Yifan; Yang, Gaoqiang; Yu, Shule; Kang, Zhenye; Mo, Jingke; Han, Bo; Talley, Derrick A.; Zhang, Feng-Yuan
Abstract: The development of water electrolyzer is challenging as we approach theoretical limits arising from electrochemical reactions and micro-scale bubble dynamics. In this research, two-phase flow and bubble dynamics are in-situ studied in a special designed single-channel electrolyzer. The devices fabricated by a 3D printer provide a whole vision of the electrochemical reaction within the channel. In-situ observations of channel-scale hydrogen and oxygen micro-bubbles dynamics are conducted, and the whole process of hydrogen evolution reactions (HERs) and oxygen evolution reactions (OERs) are simultaneously studied. The results indicate that all bubbles generate at the interface between the proton exchange membrane and the electrode wire, and the operating conditions have a great impact on the micro bubble evolution process. The bubble detachment diameter is inversely proportional to the flow velocity, but is in direct proportion to the current density. Finally, a mathematic model has been developed, and shows a good agreement with experimental data. Those results could help to better understand the bubble evolution mechanism, in order to further understand the electrochemical reaction. Graphical abstract: Image 1 Highlights: A novel device is developed to study electrochemical reaction processes. Microscale hydrogen/oxygen evolution reactions are visualized simultaneously. Oxygen bubble detachment diameter is larger than that of hydrogen bubble. A model shows a good agreement with experimental results.